Method of making aluminum-containing particles

By using an anti-sintering agent to control the aluminothermic reaction during the preparation of aluminum-containing particles, the problems of uneven aluminum penetration and adhesion on the particle surface were solved, achieving uniform aluminum penetration and easy-to-recycle particle manufacturing.

CN116529001BActive Publication Date: 2026-11-06AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180079716.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-04
Filing Date
2021-11-30
Publication Date
2026-11-06
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

In existing technologies, when preparing aluminum-containing particles, there are areas on the particle surface that are not permeated with aluminum, which prevents them from exhibiting the expected properties. Furthermore, they tend to form lumpy adhesions during the aluminothermic reaction, making it difficult to recover the aluminized particles.

Method used

A mixture of particles containing heavy metals to be treated, an aluminum source, a halide-containing activator, and an anti-sintering agent is used. Aluminizing is performed through the gaps in the anti-sintering agent to control the heat of the aluminothermic reaction and prevent adhesion. The aluminized particles are then recovered by removing the anti-sintering agent.

Benefits of technology

It enables the production of particles that are uniformly infiltrated with aluminum across the entire surface, avoiding blocky adhesion and simplifying the recycling process of the infiltrated particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116529001B_ABST
    Figure CN116529001B_ABST
Patent Text Reader

Abstract

A method for producing a particle, a treated particle containing a heavy metal having a specific gravity of 4 or more, an aluminum source, an active agent containing a halide, and an anti-sintering agent are mixed to obtain a mixed particle, the mixed particle is heated, the treated particle is subjected to aluminizing treatment using a gap between the anti-sintering agents formed by the anti-sintering agent, and a treated mixed material containing an aluminized particle is obtained, the anti-sintering agent is removed from the treated mixed material, and the aluminized particle is recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing aluminum-containing particles. Background Technology

[0002] Aluminum-containing particles have excellent oxidation resistance at high temperatures and can be used for various applications.

[0003] For example, reference 1 describes the use of particles containing intermetallic compound phases of iron and aluminum as thermal spraying raw materials to perform atmospheric plasma thermal spraying, forming an iron-aluminum intermetallic compound film on the surface of stainless steel.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. WO2018 / 116856 Summary of the Invention

[0007] The particles cited in reference 1 were prepared by high-temperature sintering of a mixture of powder containing an iron-aluminum intermetallic compound and iron-containing powder.

[0008] However, the inventors of this application observed that the particles prepared using this method have regions on their surface where aluminum is absent. With particles containing such surface regions lacking aluminum, the desired properties cannot be achieved.

[0009] The present invention was made in view of the following background, and the object of the present invention is to provide a method for manufacturing particles containing aluminum throughout the entire surface.

[0010] This invention provides a method for manufacturing aluminum-containing particles, comprising mixing particles containing a heavy metal with a specific gravity of 4 or more, an aluminum source, a halide-containing activator, and an anti-sintering agent to obtain mixed particles, heating the mixed particles, and using the gaps between the anti-sintering agents formed by the anti-sintering agents to perform aluminizing treatment on the particles to obtain a finished mixture containing aluminized particles, removing the anti-sintering agent from the finished mixture, and recovering the aluminized particles.

[0011] This invention provides a method for manufacturing aluminum particles that are permeated throughout the entire surface. Attached Figure Description

[0012] Figure 1 This is a diagram illustrating an example of a process for manufacturing particles according to one embodiment of the present invention.

[0013] Figure 2 This is a schematic diagram illustrating the process of filling a reaction vessel with mixed particles.

[0014] Figure 3 This is a diagram showing a cross-section ((a)) of a spherical particle obtained in one embodiment of the present invention, and the distribution of aluminum contained in the cross-section ((b)).

[0015] Figure 4 This is a diagram showing a cross-section ((a)) of a spherical particle obtained in another embodiment of the present invention, and the distribution of aluminum contained in the cross-section ((b)).

[0016] Figure 5 This is a diagram showing a cross section ((a)) of a spherical particle obtained in another embodiment of the present invention, and the distribution of aluminum contained in the cross section ((b)).

[0017] Figure 6 This is a diagram showing a cross section ((a)) of a spherical particle obtained in another embodiment of the present invention, and the distribution of aluminum contained in the cross section ((b)).

[0018] Figure 7 This is a diagram showing a cross section ((a)) of a spherical particle obtained in another embodiment of the present invention, and the distribution of aluminum contained in the cross section ((b)).

[0019] Figure 8 This is a diagram showing a cross section ((a)) of a spherical particle obtained in another embodiment of the present invention, and the distribution of aluminum contained in the cross section ((b)).

[0020] Figure 9 This is a diagram showing a cross section ((a)) of a spherical particle obtained in another embodiment of the present invention, and the distribution of aluminum contained in the cross section ((b)). Detailed Implementation

[0021] Hereinafter, one embodiment of the present invention will be described.

[0022] As mentioned above, the particles in cited reference 1 have regions on their surface where aluminum is absent. For particles with such surface regions lacking aluminum, the desired properties may not be achieved.

[0023] As a solution to the problem of insufficient aluminum on the surface, aluminum diffusion treatment of the particles to be treated can be considered.

[0024] Aluminizing is a technique that allows aluminum to diffuse into the surface of a plate-shaped or block-shaped object at high temperatures. For example, when the object contains iron, a uniform iron-aluminum alloy can be formed on the surface of the object after aluminizing.

[0025] However, if aluminizing is applied to a material containing trace amounts of oxygen, the reduction of oxides in the material and the oxidation of aluminum will occur, causing a solid-phase contact reaction (aluminothermic reaction) accompanied by a large amount of heat generation. If an aluminothermic reaction occurs, the reaction will accelerate due to heating, and the heat will accumulate before it can be released. As a result, the reaction system will reach a high temperature of several thousand degrees Celsius.

[0026] Therefore, if the material being processed is in particle form, and an aluminothermic reaction occurs, the processing environment becomes extremely hot, and the processed mixture (hereinafter referred to as the "processed mixture") becomes a blocky form in which all the particles are firmly adhered to each other.

[0027] Furthermore, once such a blocky processed mixture is formed, the anti-sintering agent cannot be separated from the processed mixture. Therefore, there is a problem that the aluminizing particles (hereinafter also referred to as "aluminized particles") cannot be recovered from the processed mixture.

[0028] In contrast, in one embodiment of the present invention, a method for manufacturing aluminum-containing particles is provided, wherein a particle to be treated containing a heavy metal with a specific gravity of 4 or more, an aluminum source, a halide-containing activator, and an anti-sintering agent are mixed to obtain a mixed particle; the mixed particle is heated; the particle to be treated is aluminized using the gaps between the anti-sintering agents formed by the anti-sintering agents; a treated mixture containing aluminized particles is obtained; the anti-sintering agent is removed from the treated mixture; and the aluminized particles are recovered.

[0029] Here, "heavy metals with a specific gravity of 4 or higher" include iron, chromium, nickel, molybdenum, bismuth, tungsten, cobalt, zirconium, manganese, and copper, etc.

[0030] In addition, the "processed particles" are not limited to a single metal, but can also be alloys containing the above-mentioned elements.

[0031] According to one embodiment of the present invention, the particles to be treated are subjected to aluminum impregnation using an aluminizing process. Alternatively, according to another embodiment of the present invention, the aluminizing process is performed using the gaps formed between anti-sintering agents.

[0032] Due to these characteristics, in one embodiment of the method of the present invention, even if an aluminothermic reaction occurs within the reaction system, the likelihood of the treated particles adhering to the anti-sintering agent and / or other treated particles can be greatly reduced. This is because the aforementioned gaps function as providing numerous mutually separated "small regions" for the reaction.

[0033] As a result, the treated mixture after aluminizing does not completely agglomerate into a blocky form, but rather remains in a state where the aluminizing particles and the anti-sintering agent are separated. Therefore, in one embodiment of the method of the present invention, the anti-sintering agent can be removed relatively easily from the treated mixture after aluminizing. This also allows for relatively easy recovery of the aluminizing particles.

[0034] Thus, in one embodiment of the method of the present invention, the particles being treated can be subjected to aluminizing treatment in a reasonable manner, and particles containing aluminum throughout their entire surface can be reasonably manufactured.

[0035] (A method for manufacturing particles according to one embodiment of the present invention)

[0036] Next, with reference to the accompanying drawings, a method for manufacturing particles according to one embodiment of the present invention will be described.

[0037] Figure 1 The diagram illustrates an example of a process for manufacturing particles according to one embodiment of the present invention.

[0038] like Figure 1 As shown, a method for manufacturing particles according to one embodiment of the present invention (hereinafter referred to as the "first manufacturing method") includes: a step of preparing a mixed particle comprising a particle to be treated, an aluminum source, an activator and an anti-sintering agent (S110); a step of heating the mixed particle to perform an aluminizing treatment on the particle to be treated (S120); and a step of removing the anti-sintering agent (S130).

[0039] The following is a more detailed explanation of each process.

[0040] (Process S110)

[0041] First, prepare hybrid particles.

[0042] The mixed particles include the particles to be treated, an aluminum source, an activator, and an anti-sintering agent. The individual particles are described below.

[0043] (Particles being processed)

[0044] The treated particles contain heavy metals with a specific gravity of 4 or higher, as described above. These heavy metals may include, for example, at least one element selected from iron, chromium, nickel, molybdenum, bismuth, tungsten, cobalt, zirconium, manganese, and copper.

[0045] Furthermore, the particles being treated are not limited to a single metal, but can also be alloys containing the aforementioned elements. For example, the particles being treated can also be stainless steel particles or iron-aluminum alloy particles.

[0046] Furthermore, in addition to heavy metals with a specific gravity of 4 or higher, the particles being treated may also contain unavoidable impurities. Examples of unavoidable impurities include phosphorus, sulfur, and carbon.

[0047] It should be noted that, for clarity, the first manufacturing method will be described in the following explanation, for example, using the case where the processed particles are iron (containing unavoidable impurities). In this case, manganese, phosphorus, sulfur, and carbon can be cited as unavoidable impurities.

[0048] The average particle size of the treated particles is selected to be smaller than the average particle size of the anti-sintering agent described later. For example, the maximum particle size of the treated particles may be less than 0.29 times the average particle size of the anti-sintering agent.

[0049] The particle size of the processed particles can be, for example, in the range of 10 μm to 600 μm.

[0050] It should be noted that in this application, the "average particle size" was determined according to the method specified in JIS Z 8801.

[0051] That is, multiple sieves of different aperture sizes are stacked sequentially, starting with the smallest aperture, and the particles to be measured are vibrated with a certain amplitude for a certain period of time to separate the particles. Then, the mass of the particles remaining on each sieve is measured, and a particle size distribution chart of the particle mass is plotted. The particle size corresponding to 50% of the cumulative value of the obtained particle size distribution is determined as the "average particle size".

[0052] The particle size of the processed particles is represented by the range of minimum and maximum values.

[0053] (Aluminum source)

[0054] The aluminum source can be aluminum metal particles or aluminum alloy particles.

[0055] The average particle size of the aluminum source is selected to be smaller than the average particle size of the anti-sintering agent. For example, the average particle size of the aluminum source can be less than 0.29 times the average particle size of the anti-sintering agent.

[0056] The average particle size of the aluminum source can be, for example, in the range of 10 μm to 600 μm.

[0057] It should be noted that the average particle size of the aluminum source is preferably smaller than the average particle size of the particles being treated.

[0058] (Active agent)

[0059] The activator has the function of forming metal halide vapors and promoting the aluminizing process during the aluminizing process of the treated particles.

[0060] The surfactant contains at least one of, for example, ammonium chloride, ferric chloride, aluminum chloride, ferric fluoride, and aluminum fluoride. The surfactant is added in the range of, for example, 0.1% to 2% by mass relative to the total amount of the mixed particles.

[0061] (Anti-sintering agent)

[0062] Anti-sintering agents may contain at least one of alumina, kaolin, and silicon dioxide.

[0063] The anti-sintering agent may have at least one shape selected from, for example, spherical, triangular pyramidal, triangular prismal, tetrahedral, conical and cylindrical.

[0064] It should be noted that the anti-sintering agent has a sufficiently large average particle size compared to the treated particles and the aluminum source. For example, the average particle size of the anti-sintering agent can be selected to be more than 3.4 times the maximum particle size of the treated particles and the average particle size of the aluminum source.

[0065] The average particle size of the anti-sintering agent can be in the range of, for example, 500 μm to 5000 μm.

[0066] (Mixed particles)

[0067] Mixed particles are prepared by mixing the above-mentioned components.

[0068] The amount of treated particles contained in the mixed particles is, for example, in the range of 10% to 40% by mass. Additionally, the amount of aluminum source contained in the mixed particles is, for example, in the range of 2% to 20% by mass. Furthermore, the amount of anti-sintering agent contained in the mixed particles is, for example, in the range of 40% to 80% by mass.

[0069] (Process S120)

[0070] Next, the mixed particles prepared in step S110 are subjected to heat treatment. Therefore, the mixed particles can be filled into the reaction vessel.

[0071] The particles are aluminized by heating the reaction vessel. That is, aluminum generated from the aluminum source diffuses into the particles being treated, forming aluminized particles.

[0072] Here, the greater the difference in ionization tendency between the treated agent contained in the mixed particles and the aluminum source, the greater the heat generated by the aluminothermic reaction between the mixed particles when the reaction vessel is heated. This is because aluminum reacts with the trace amounts of oxygen contained in the treated particles, thereby reducing the treated particles.

[0073] If such an aluminothermic reaction occurs, the reaction vessel becomes extremely hot, and the treated mixture, i.e., the "processed mixture," becomes a blocky form in which all the particles are firmly adhered to each other. Moreover, once such a blocky processed mixture is formed, the problem arises that the anti-sintering agent cannot be separated from the processed mixture later.

[0074] In contrast, the formation of lumpy mixtures can be significantly suppressed in the first manufacturing method.

[0075] The following is for reference. Figure 2 This feature will be explained.

[0076] Figure 2 This schematically illustrates an example of the morphology of mixed particles when they are filled into a reaction vessel. For example... Figure 2 As shown, the reaction vessel is filled with the treated particles 352, aluminum source 354, activator, and anti-sintering agent 358, which are components of the mixed particles.

[0077] It should be explained that Figure 2 Surfactants are omitted here. Furthermore, it is assumed that all components of the mixed particles are spherical.

[0078] Here, when the diameter of the anti-sintering agent 358 (in φ) S (represented by) and the diameter of the processed particle 352 (in φ) Fe (indicated) and the diameter of aluminum source 354 (in φ) Al When the concentration is sufficiently large, voids 365 are created between adjacent anti-sintering agents 358. Additionally, the treated particles 352 and the aluminum source 354 are disposed within the voids 365 created by the anti-sintering agent 358.

[0079] When the reaction vessel is heated with the mixed particles in this configuration, the likelihood of adhesion between the treated particles 352 and the anti-sintering agent 358 and / or other treated particles 352 is greatly reduced, even if an aluminothermic reaction occurs within the reaction vessel. This is because the voids 365 act as numerous "small zones" for the aluminizing process.

[0080] As a result, the treated mixture produced after heat treatment does not completely agglomerate into a blocky form, but rather remains in a state where the aluminizing particles and the anti-sintering agent 358 are separated. Therefore, in subsequent processes, the aluminizing particles can be recovered from the treated mixture.

[0081] Table 1 below shows examples of fillings with mixed particles that can exhibit the effects described above.

[0082] Here, it is assumed that the particle being treated, 352, is a spherical iron particle (density 7.87 g / cm³). 3Aluminum source 354 consists of spherical aluminum particles (density 2.70 g / cm³). 3 The surfactant is spherical ammonium chloride particles (density 1.527 g / cm³). 3 Anti-sintering agent 358 is spherical alumina (density 4.00 g / cm³). 3 ).

[0083] Additionally, assuming the average particle size φ of anti-sintering agent 358 is... S The particle size φ of the treated particles 352 is 1000 μm. Fe The average particle size φ of aluminum source 354 ranges from 38μm to 75μm. Al The particle size is 50 μm, and the average particle size of the surfactant is 10 μm.

[0084] [Table 1]

[0085]

[0086] According to Table 1, when 10 kg of anti-sintering agent 358 is filled in the densest manner, anti-sintering agent 358 occupies 74% of the total space volume. Therefore, the void space 365 is 26%.

[0087] When the void 365 is completely (100%) filled with the treated particles 352, the aluminum source 354 and the activator, for example, the amount of the treated particles 352 is 2.216 kg, the amount of the aluminum source 354 is 1.491 kg and the amount of the activator is 0.067 kg.

[0088] Similarly, when 85% of the void 365 is filled with the treated particles 352, the aluminum source 354, and the activator, the amount of the treated particles 352 can be calculated to be 1.879 kg, the amount of the aluminum source 354 to be 1.253 kg, and the amount of the activator to be 0.066 kg.

[0089] It should be noted that in the above calculations, it is assumed that the Al / Fe ratio in the mixed particles is 40 / 60 (mass ratio). Additionally, it is assumed that the amount of surfactant is 0.5 wt% of the total.

[0090] When the anti-sintering agent 358 is filled in a form other than the densest filler, the amount of each component can also be calculated in the same way.

[0091] It should be noted that when the anti-sintering agent 358 is spherical, in order to obtain the above-mentioned effect, the filling rate of the anti-sintering agent 358 is preferably in the range of 55% to 74% (when the filling is densest).

[0092] Furthermore, in the voids 365 created by the anti-sintering agent 358, the filling rate of the treated particles 352, the aluminum source 354, and the activator is preferably in the range of 60% to 100%.

[0093] In practice, assuming that the anti-sintering agent 358 is non-spherical, the preferred range for the filling rate of the anti-sintering agent 358 is set to 50% to 80%.

[0094] Therefore, in the first manufacturing method, the particles 352 being treated can be aluminized using the voids 365 created between the anti-sintering agents 358.

[0095] The processing atmosphere for aluminizing can be any oxygen-free, inactive atmosphere, such as an argon atmosphere.

[0096] There is no particular limitation on the processing temperature, as long as aluminum diffusion and penetration into the particles being processed occurs. The processing temperature can be, for example, in the range of 800℃ to 1100℃.

[0097] There is no specific time limit for processing, for example, it can be within the range of 1 to 10 hours.

[0098] (Process S130)

[0099] Next, the anti-sintering agent is removed from the powdered processed mixture formed in step S120. For example, the processed mixture can be sieved using a sieve that can only pass through particles with a small average particle size, thereby removing the anti-sintering agent.

[0100] As described above, in the first manufacturing method, the high temperature of the reaction system caused by the accumulation of excessive heat generated in the aluminothermic reaction can be significantly suppressed.

[0101] Therefore, in the first manufacturing method, the anti-sintering agent and the aluminizing particles can be separated relatively easily.

[0102] Through the above processes, particles containing aluminum throughout the entire surface can be reasonably manufactured in the first manufacturing method.

[0103] Example

[0104] Hereinafter, embodiments of the present invention will be described. It should be noted that in the following description, Examples 1 to 7 are embodiments, and Example 11 is a comparative example.

[0105] (Example 1)

[0106] Aluminized iron particles are produced using the following method.

[0107] First, iron particles (10.96 wt%), aluminum particles (10.96 wt%), ammonium chloride particles (0.50 wt%), and spherical alumina particles (77.58 wt%), which are used as the particles to be treated, are thoroughly mixed to prepare mixed particles.

[0108] The iron particles have a diameter of 38 μm to 75 μm, the aluminum particles have an average diameter of 50 μm, the activator has a diameter of 10 μm, and the alumina particles have a diameter of 1000 μm.

[0109] The mixed particles were filled into a heat-resistant container. The calculated alumina particle filling rate was 74%. Additionally, iron, aluminum, and ammonium chloride particles were added, making them occupy 85% of the remaining 26% of the void space.

[0110] Next, the heat-resistant container was replaced with an argon atmosphere and then heated at 1000°C. After maintaining the temperature at 1000°C for 10 hours, the heat-resistant container was furnace cooled.

[0111] The processed mixture was then removed from the heat-resistant container and the alumina powder was removed using a #32 mesh sieve. This yielded spherical particles (hereinafter referred to as "particles of Example 1").

[0112] (Example 2)

[0113] Iron particles that have undergone aluminizing treatment were produced using the same method as in Example 1 (hereinafter referred to as "particles of Example 2").

[0114] In Example 2, the mixed particles contained 13.20% by mass of iron particles, 9.96% by mass of aluminum particles, 0.5% by mass of ammonium chloride particles as an activator, and 76.34% by mass of spherical alumina particles as an anti-sintering agent.

[0115] The filling rate of alumina particles and other conditions are the same as in Example 1.

[0116] (Example 3)

[0117] Iron particles that have undergone aluminizing treatment were produced using the same method as in Example 1 (hereinafter referred to as "particles of Example 3").

[0118] In Example 3, the mixed particles contained 14.24% by mass of iron particles, 9.49% by mass of aluminum particles, 0.5% by mass of ammonium chloride particles as an activator, and 75.77% by mass of spherical alumina particles as an anti-sintering agent.

[0119] The filling rate of alumina particles and other conditions are the same as in Example 1.

[0120] (Example 4)

[0121] Iron particles that have undergone aluminizing treatment were produced using the same method as in Example 1 (hereinafter referred to as "particles of Example 4").

[0122] In Example 4, the mixed particles contained 15.71% by mass of iron particles, 8.83% by mass of aluminum particles, 0.5% by mass of ammonium chloride particles as an activator, and 74.96% by mass of spherical alumina particles as an anti-sintering agent.

[0123] The filling rate of alumina particles and other conditions are the same as in Example 1.

[0124] (Example 5)

[0125] Iron particles that have undergone aluminizing treatment were produced using the same method as in Example 1 (hereinafter referred to as "particles of Example 5").

[0126] In Example 5, the mixed particles contained 16.87% by mass of iron particles, 8.31% by mass of aluminum particles, 0.5% by mass of ammonium chloride particles as an activator, and 74.32% by mass of spherical alumina particles as an anti-sintering agent.

[0127] The filling rate of alumina particles and other conditions are the same as in Example 1.

[0128] (Example 6)

[0129] Iron particles that have undergone aluminizing treatment were produced using the same method as in Example 1 (hereinafter referred to as "particles of Example 6").

[0130] In Example 6, the mixed particles contained 17.69% by mass of iron particles, 7.95% by mass of aluminum particles, 0.5% by mass of ammonium chloride particles as an activator, and 73.87% by mass of spherical alumina particles as an anti-sintering agent.

[0131] The filling rate of alumina particles and other conditions are the same as in Example 1.

[0132] (Example 7)

[0133] Iron particles that have undergone aluminizing treatment were produced using the same method as in Example 1 (hereinafter referred to as "particles of Example 7").

[0134] In Example 7, the mixed particles contained 22.74% by mass of iron particles, 5.68% by mass of aluminum particles, 0.5% by mass of ammonium chloride particles as an activator, and 71.08% by mass of spherical alumina particles as an anti-sintering agent.

[0135] The filling rate of alumina particles and other conditions are the same as in Example 1.

[0136] (Example 11)

[0137] Try to produce aluminized iron particles using the same method as in Example 1.

[0138] In Example 11, the mixed particles contained iron particles with an average particle size of 50 μm, aluminum particles with an average particle size of 50 μm, and alumina particles with an average particle size of 60 μm. Furthermore, the mixed particles contained 56.00% by mass of iron particles, 24.00% by mass of aluminum particles, 0.50% by mass of ammonium chloride particles (as an activator), and 19.50% by mass of alumina particles.

[0139] The heating temperature is 1000℃ and the heating time is 10 hours.

[0140] The processed mixture obtained after heat treatment is in block form, making it difficult to separate and remove alumina particles.

[0141] Table 2 below summarizes the content and particle size of each component in the mixed particles used in each example.

[0142] [Table 2]

[0143]

[0144] In addition, Table 3 below summarizes the alumina particle filling rate and the filling rate of other components relative to the voids in each example.

[0145] [Table 3]

[0146]

[0147] It should be noted that in Example 11, the particle size of the alumina particles is almost the same as that of the other components, so the filling rate is omitted.

[0148] (evaluate)

[0149] Particle morphology was observed using the particles from each example.

[0150] (Cross-section analysis)

[0151] Using the particles from each example, prepare specimens for cross-sectional observation as follows.

[0152] First, multiple particles are embedded in resin, which is then allowed to cure. Next, the resin is polished using abrasive paper and a polishing device to expose the cross-sections of the particles.

[0153] It should be noted that the object of observation is a spherical particle with a "maximum cross-section". Here, "maximum cross-section" refers to the cross-section passing through the center of the spherical particle. Therefore, the particle's "maximum cross-section" has a size that is substantially the same as the particle's diameter.

[0154] Hereinafter, among the spherical particles in Examples 1 to 7, the spherical particles that are the objects of observation will be referred to as "Sample 1" to "Sample 7" respectively.

[0155] The cross-sections of the spherical particles from samples 1 to 7 were observed using SEM. Furthermore, EDX analysis was used to evaluate the amounts of iron and aluminum contained in the cross-sections of the spherical particles.

[0156] Figures 3-9 The cross section of the spherical particles obtained in each sample is shown ((a)) and the distribution of aluminum contained in the cross section is shown ((b)).

[0157] For example, Figure 3 This represents the cross-section of the spherical particles obtained in sample 1. Figure 3 (a) and the distribution of aluminum contained in the cross section ( Figure 3 (b)). Additionally... Figure 4 This represents the cross-section of the spherical particles obtained in sample 2. Figure 4 (a) and the distribution of aluminum contained in that cross section ( Figure 4 (b)), and the same applies below.

[0158] It should be noted that in each sample, the distribution of iron in the cross-section is the reverse of the distribution of aluminum.

[0159] according to Figures 3-9 It can be seen that in any one of samples 1 to 7, aluminum is impregnated on the entire surface of the particle.

[0160] Next, energy-scattered X-ray (EDX) analysis was performed on the cross sections obtained from each sample to evaluate the concentration of aluminum and iron in the entire cross section of the particle.

[0161] Table 4 below summarizes the analytical results obtained for each sample.

[0162] [Table 4]

[0163]

[0164] The results show that the amount of aluminum contained in any individual particle is almost equal to the amount of aluminum contained in the mixed particles.

[0165] This application claims priority to Japanese Patent Application No. 2020-202260, filed on December 4, 2020, the entirety of which is incorporated herein by reference.

[0166] Explanation of reference numerals in the attached figures

[0167] 352 processed particles

[0168] 354 Aluminum Source

[0169] 358 Anti-sintering agent

[0170] 365 gaps

Claims

1. A method for manufacturing aluminum-containing particles, comprising mixing particles containing a heavy metal with a specific gravity of 4 or higher, an aluminum source, a halide-containing activator, and an anti-sintering agent to obtain mixed particles. The treated particles and the aluminum source are positioned in the gaps created between adjacent anti-sintering agents. The mixed particles are heated, and the particles are aluminized by utilizing the gaps as small reaction zones for separation, resulting in a processed mixture containing aluminized particles. Remove the anti-sintering agent from the treated mixture and recover the aluminized particles. The average particle size of the treated particles is smaller than the average particle size of the anti-sintering agent. The average particle size of the aluminum source is smaller than the average particle size of the anti-sintering agent.

2. The method according to claim 1, wherein, The mixed particles are filled into the reaction vessel, and the filling rate of the anti-sintering agent relative to the volume of the reaction vessel is in the range of 50% to 80%.

3. The method according to claim 1 or 2, wherein, The anti-sintering agent has at least one shape selected from spherical, triangular prism, tetrahedral, conical, and cylindrical.

4. The method according to claim 3, wherein, The tetrahedron shape is a triangular pyramid.

5. The method according to claim 1 or 2, wherein, The anti-sintering agent contains at least one of alumina, kaolin, and silicon dioxide.

6. The method according to claim 1 or 2, wherein, The maximum particle size of the treated particles is less than 0.29 times the average particle size of the anti-sintering agent.

7. The method according to claim 1 or 2, wherein, The average particle size of the aluminum source is less than 0.29 times the average particle size of the anti-sintering agent.

8. The method according to claim 1 or 2, wherein, The particle size of the processed particles is in the range of 10 μm to 600 μm.

9. The method according to claim 1 or 2, wherein, The average particle size of the anti-sintering agent is in the range of 500 μm to 5000 μm.

10. The method according to claim 1 or 2, wherein, The heavy metal contains at least one selected from iron, chromium, nickel, molybdenum, bismuth, tungsten, cobalt, zirconium, manganese, and copper.

Citation Information

Patent Citations

  • Wafer processing method

    JP2020202260A

  • Method for forming sprayed film of intermetallic compound film, sprayed film, method for producing metal product having sprayed film, and glass conveying roll

    WO2018116856A1

  • Treatment of metals for coating or activation

    CA2073058A1